Perancangan Sistem Informasi Berbasis Web untuk Manajemen Transaksi Penjualan dan Persediaan di Mediatama Cell - Robby Mukthar (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The rapid development of information technology has driven transformation in various aspects of human life, including the business world. Mediatama Cell, a store that operates in the sale of cellphones, vouchers, and accessories, faces challenges in managing sales transactions and inventory manually. The manual process of recording transactions and managing inventory often leads to problems such as data inaccuracies, recording errors, and difficulties in monitoring stock in real-time. This research aims to design a web-based information system that can help simplify the process of recording sales transaction data and managing inventory at Mediatama Cell. The system is designed to increase the store's operational efficiency, reduce errors in transaction recording, and facilitate easier stock monitoring. The methodology used in this research includes data analysis, requirements gathering, and system design. The result of this research is an integrated information system design that can help Mediatama Cell automatically record transactions and manage inventory more efficiently. With this system design, it is expected that Mediatama Cell can improve operational performance and provide better service to customers.